Prevalence and mortality trends of hemoglobinopathies in Italy: a nationwide study - Barbara Gianesin; Frédéric B. Piel; Khaled M. Musallam; Susanna Barella; Maddalena Casale; Elena Cassinerio; Rosario Di Maggio; Antonia Gigante; Maria Rita Gamberini; Giovanna Graziadei; Roberto Lisi; Filomena Longo; et al. (Haematologica)
Not available.